The Role of Qualitative Characteristics of Accounting Information in the Realization of Competitive Strategies: An Analytical Study for the Eyes of a Private Finance Manager in Erbil/Kurdistan Region-Iraq - صابر شيخه, نصرت (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The research seeks to know the relationship and impact of the qualitative characteristics of accounting information, represented by (suitability, reliability), in the competitive strategies represented by (comprehensive cost leadership strategy, excellence strategy, focus strategy). The general framework of the research represented by defining the problem by raising several questions about the qualitative characteristics of accounting information and the nature of the relationship and the impact between it and competitive strategies. For this purpose, a hypothesis scheme was designed, from which two main hypotheses emerged, and in order to ensure their validity, they were subjected to multiple tests. The research followed the descriptive analytical approach, as the main and sub-variables were described, as well as the analysis of relationships and influence between the variables. The research community represented all the managers of private banks in the city of Erbil, the Kurdistan Region of Iraq, and their number was (195). The sample consisted of (96) managers. The two hypotheses were tested through a set of statistical tests using the computer program (SPSS V.23). The research reached a set of conclusions, the most important of which is the existence of high correlations and strong influences between the main and sub-variables, at the macro and micro levels. The research suggested a set of proposals in the light of the conclusions, including the need to harness the strong relationships between the two variables and their orientation towards serving the surveyed banks with the need to document the relationship between each of the characteristics of accounting information and competitive strategies.